A Community Jury on initiating weight management conversations in primary care. (21st June 2021) - Beeken, Rebecca J.; Scott, Anna M.; Sims, Rebecca; Cleo, Gina; Clifford, Helen; Glasziou, Paul; Thomas, Rae
Abstract: Background: Current guidelines recommend that patients attending general practice should be screened for excess weight, and provided with weight management advice. Objective: This study sought to elicit the views of people with overweight and obesity about the role of GPs in initiating conversations about weight management. Methods: Participants with a body mass index ≥25 were recruited from a region in Australia to take part in a Community Jury. Over 2 days, participants (n = 11) deliberated on two interconnected questions: 'Should GPs initiate discussions about weight management?' And 'if so, when: (a) opportunistically, (b) in the context of disease prevention, (c) in the context of disease management or (d) other?' The jury deliberations were analysed qualitatively to elicit their views and recommendations. Results: The jury concluded GPs should be discussing weight management, but within the broader context of general health. The jury were divided about the utility of screening. Jurors felt GPs should initiate the conversation if directly relevant for disease prevention or management, otherwise GPs should provide opportunities for patients to consent to the issue being raised. Conclusion: The jury's verdict suggests informed people affected by overweight and obesity believe GPs should discuss weight management with their patients. GPs should feel reassured that discussions are likely to be welcomed by patients, particularly if embedded within a more holistic focus on person‐centred care. Public contribution: Members of the public took part in the conduct of this study as jurors, but were not involved in the design, analysis or write‐up.